Investigating the Gap Between Viewers’ Perception and Artists’ Motifs of the Graffiti Art in Bangladesh: An Inquiry (Journal of the Asiatic Society of Bangladesh, Humanities, 2026)
Following the Anti-Discrimination Student Movement (ADSM) in Bangladesh, graffiti art has suddenly begun to overflow all the walls of the country's main cities, like a gigantic stream. This city-based art form is widely recognised for its multifaceted functions, ranging from protest against any injustice to celebrating national and international achievements. In short, apart from its artistic value, this art can also play an educational role, uphold tradition, and make historical sense through its distinctive potential. Therefore, forming a correct perception by readers is crucial; otherwise, people in general may be misled by the discourse displayed in public graffiti. Focusing on this issue, the present study aims to identify the gap between viewers' perceptions and artists’ motifs regarding the ideology-contained discourses of street art in Bangladesh in 2024, through an embodied inquiry within a mixed-method research framework. Following purposive sampling, participants (graffiti artists and viewers) were selected for the Focus Group Discussion (FGD). In addition, graffiti has been collected from the Dhaka University area and the Science Lab intersection at the researchers’ convenience for content analysis. The findings support viewers’ appropriate awareness regarding the motifs of the street art discourse.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 70(2), December 2025, pp. 155-170